2023
DOI: 10.1200/jco.2023.41.16_suppl.8030
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of abatacept, ixazomib, and dexamethasone in patients with relapsed/refractory multiple myeloma.

Abstract: 8030 Background: Multiple myeloma (MM) usually responds to induction therapy but relapses with therapy-resistant disease. CD28 expressed on MM cells is correlated with worse outcomes. Bone marrow stromal cells expressing CD28 ligands CD80 and/or CD86 are cellular partners in the MM niche transducing a pro-survival signal to MM cells contributing to therapy resistance in relapsed disease. We have previously shown in in vitro and in vivo preclinical studies that blocking the pro-survival CD28 activation on MM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, achieving long-term remissions remains an ongoing challenge, with one-quarter to greater than one-half of patients experiencing myeloma relapse within one year of CAR T infusion. In this study we set out to determine whether CD28 blockade using abatacept could sensitize MM cells to CAR T cell therapy in a manner analogous to standard chemotherapy 45,46,50 . In contrast to expectations, we found that abatacept limited efficacy of clinically relevant BCMA targeted, 4-1BB co-stimulated CAR T cells in an established human xenograft myeloma mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, achieving long-term remissions remains an ongoing challenge, with one-quarter to greater than one-half of patients experiencing myeloma relapse within one year of CAR T infusion. In this study we set out to determine whether CD28 blockade using abatacept could sensitize MM cells to CAR T cell therapy in a manner analogous to standard chemotherapy 45,46,50 . In contrast to expectations, we found that abatacept limited efficacy of clinically relevant BCMA targeted, 4-1BB co-stimulated CAR T cells in an established human xenograft myeloma mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recently reported ~3-fold improvement in overall response rate when abatacept was added to standard of care therapy 50 , we hypothesized that systemic blockade of CD28 would similarly sensitize MM to CAR T cell therapy. We reasoned that unlike endogenous T cells that require CD28 co-stimulation to mount an anti-tumor response, second generation CAR T cells receive co-stimulation directly from the CAR and would therefore be relatively unaffected by blockade of endogenous CD28.…”
Section: Introductionmentioning
confidence: 99%